The Ecological Bases for Lake and Reservoir Management 1999
DOI: 10.1007/978-94-017-3282-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect mechanisms behind successful biomanipulation

Abstract: Lake Vesijärvi is a relatively large (length 25 km; total area 110 km 2 ), shallow (mean depth 6 m), but stratified lake in southern Finland. The Enonselkä basin (26 km 2 ), surrounded by the city of Lahti, received its sewage effluent, and changed from a clear water basin with flourishing fisheries from the 1940-50s to one of the most eutrophic lake systems in Finland thereafter. In 1976, the sewage effluent was diverted, resulting in a temporary recovery of water quality. However, in the 1980s, massive surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 21 publications
(22 reference statements)
1
38
0
1
Order By: Relevance
“…, 1998; Jeppesen et al. , 1998b; Kairesalo et al. , 1999) and nutrient availability (Hansson, 1992; Persson et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 1998; Jeppesen et al. , 1998b; Kairesalo et al. , 1999) and nutrient availability (Hansson, 1992; Persson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of Lake Vesijärvi concluded that improved lake status was mainly due to direct effect of fish on nutrient concentrations and that trophic cascades were considered less important. Trophic responses were judged to result from diminished excretion and bioturbation by fish, leading to reduced fish‐mediated nutrient transfer from benthic and littoral habitats to the lake pelagic zone (Horppila et al ., ; Hansson et al ., ; Kairesalo et al ., ). The decrease in TP at the beginning of restoration supports these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, a clear water basin underwent eutrophication due to sewage effluent that emanated from the city of Lahti that surrounds the lake basin (Keto & Sammalkorpi, 1988). In the 1980s, massive cyanobacteria blooms degraded the water quality of the basin and therefore biomanipulation measures were implemented, along with diffuse load reduction, as restoration actions in the late 80s and early 90s (Kairesalo et al, 1999). Water quality improved, but within 10 years, cyanobacteria blooms had occurred again (Keto et al, 2005).…”
Section: Study Areamentioning
confidence: 99%